John Frank Stevens : Civil Engineer. - Foust, Clifford (Railroads past and present., 2013)
One of America's foremost civil engineers of the past 150 years, John Frank Stevens was a railway reconnaissance and location engineer whose reputation was made on the Canadian Pacific and Great Northern lines. Self-taught and driven by a bulldog tenacity of purpose, he was hired by Theodore Roosevelt as chief engineer of the Panama Canal, creating a technical achievement far ahead of its time. Stevens also served for more than five years as the head of the US Advisory Commission of Railway Experts to Russia and as a consultant who contributed to many engineering feats, including the contro.